Updates to the RIFM Criteria Document for fragrance ingredient evaluation - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-propanol, 1,1′,1′,1'-(1,2-ethanediyldinitrilo)tetrakis-, CAS Registry Number 102-60-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, octyl crotonate, CAS Registry Number 22874-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, propenylguaethol, CAS Registry Number 94-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxybutyrate, CAS Registry Number 5405-41-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(p-tert-butylphenyl)-2-methylpropanol, CAS Registry Number 56107-04-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxyhexanoate, CAS Registry Number 2305-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, linoleic acid, CAS Registry Number 60-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-naphthyl isobutyl ether, CAS Registry Number 2173-57-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,5-dimethylhexyl acetate, CAS Registry Number 67952-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-pentenyl)-3-cyclohexene-1-carbonitrile, CAS Registry Number 68084-04-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexaneethyl acetate, CAS Registry Number 21722-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3,5,5-trimethylcyclohexanol, CAS Registry Number 116-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 5-methyl-2-phenyl-2-hexenal, CAS Registry Number 21834-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-heptanol, 2,6-dimethyl-,acetate, CAS Registry Number 10250-45-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, phenylacetaldehyde glyceryl acetal, CAS Registry Number 29895-73-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanemethanol, 2,4-dimethyl-, CAS Registry Number 68480-15-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2,2,6-trimethylcyclohexanone, CAS Registry Number 2408-37-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cis-4-(isopropyl)cyclohexanemethanol, CAS registry number 13828-37-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanone, 2-ethyl-4,4-dimethyl-, CAS registry number 55739-89-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, squalene, CAS Registry Number 111-02-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-guaiene, CAS Registry Number 88-84-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3-hexene, 1,1′,''-[ethylidynestris(oxy)]tris-, (3Z, 3′Z,3"Z)-, CAS registry number 215305-10-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hydroxyhexanoate, CAS Registry Number 21188-58-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-2-phenyl-2-pentenal, CAS Registry Number 26643-91-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-phenyl-2-butenal, CAS Registry Number 4411-89-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dodecyldimethylamine oxide, CAS Registry Number 1643-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tricosane, CAS Registry Number 638-67-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonenoate, CAS registry number 111-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-(isopropyl)-β-methylcyclohexanethanol, CAS Registry Number 67634-03-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, undecanol, CAS Registry Number 30207-98-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl cis-5-octenoate, CAS Registry Number 41654-15-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-nonenoate, CAS Registry Number 13481-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methyl-3-penten-2-one, CAS Registry Number 141-79-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hexenoate, CAS Registry Number 2396-78-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone, CAS Registry Number 54464-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, docosane, CAS Registry Number 629-97-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl jasmonate, CAS Registry Number 1211-29-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS Registry Number 63500-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dimyrcene, CAS Registry Number 532-87-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl myristate, CAS Registry Number 124-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2,4-bis(1-methylethenyl)-, (1R,2R,4S)-rel-, CAS Registry Number 33880-83-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl myristate, CAS Registry Number 124-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-methylpentyl 2-methylvalerate, CAS Registry Number 90397-38-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pyrazine, methyl (methylthio)-, CAS Registry Number 67952-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-propenoic acid, 2-[1-(3,3-dimethylcyclohexyl)ethoxy]-2-methylpropyl ester, CAS Registry Number 820975-49-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecyl palmitate, CAS Registry Number 540-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2-(1-methylethenyl)-4-(1-methylethyl)-, didehydro derivative, CAS Registry Number 68845-33-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, butyl sulfide, CAS Registry Number 544-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heneicosane, CAS Registry Number 629-94-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl palmitate, CAS Registry Number 628-97-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, sclareol, CAS registry number 515-03-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl octadecanoate, CAS Registry Number 111-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexyl methyl pentanone, CAS Registry Number 4927-39-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heptadecane, CAS Registry Number 629-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecane, CAS Registry Number 544-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, oleic acid, CAS Registry Number 112-80-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pentadecane, CAS Registry Number 629-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tetradecane, CAS Registry Number 629-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, nonadecane, CAS Registry Number 629-92-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, octadecane, CAS Registry Number 593-45-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, eicosane, CAS Registry Number 112-95-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessments, ethyl ricinoleate, CAS Registry Number 55066-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-8-methylenetricyclo[3.3.1.(3,7)]decan-2-yl acetate, CAS Registry Number 122760-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

RIFM fragrance ingredient safety assessment, phytyl acetate, CAS Registry Number 10236-16-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]benzene, CAS Registry Number 67634-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2,3,5,6-tetramethylpyrazine, CAS Registry Number 1124-11-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cedryl methyl ether, CAS Registry Number 67874-81-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl 2-(formylamino)benzoate, CAS Registry Number 41270-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, naphtho[2,1-b]furan, dodecahydro-3a,6,6,9a-tetramethyl-, (3aR,5aS,9aS,9bR)-, CAS Registry Number 6790-58-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, laurel leaf oil, CAS Registry Number 8007-48-5, RIFM ID 476-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, (Z)-2-penten-1-ol, CAS Registry Number 1576-95-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-3,5-heptadien-2-one, CAS Registry Number 1604-28-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopropylphenylbutanal, CAS Registry Number 125109-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl cinnamate, CAS Registry Number 103-26-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, lovage leaf oil, CAS Registry Number 8016-31-7, RIFM ID 813-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β,β,3-trimethyl benzenepropanol, CAS Registry Number 103694-68-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-β-ionone, CAS registry number 17283-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-hexanone, CAS Registry Number 589-38-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl methylphenylglycidate, CAS Registry Number 77-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-α-ionone, CAS Registry Number 31499-72-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, hinoki root oil, CAS Registry Number 91745-97-0, RIFM ID 5487-A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobornyl methyl ether, CAS Registry Number 5331-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl safranate, CAS registry number 35044-57-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Bucchu oil, betulina, CAS Registry Number 68650-46-4, RIFM ID 73-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl pyruvate, CAS registry number 617-35-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, thyme oil, red, CAS Registry Number 8007-46-3, RIFM ID 471.E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-methyl-3-tolylpropionaldehyde, CAS Registry Number 41496-43-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dihydrocarvyl acetate, CAS Registry Number 20777-49-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2,6-nonadien-1-al, CAS Registry Number 41448-29-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopulegyl acetate, CAS Registry number 57576-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, anisyl alcohol, CAS Registry Number 105-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, bicyclo[3.1.0]hexan-3-one, 4-methyl-1-(1-methylethyl)-, CAS Registry Number 1125-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-isopropyl-2(1H)-octahydronaphthalenone, CAS Registry Number 34131-98-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl 3-phenylglycidate, CAS Registry Number 121-39-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, citral, CAS Registry Number 5392-40-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,6-octadien-3-ol, 3,7-dimethyl-, acid-isomerized, CAS Registry Number 73018-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1,1-dimethoxycyclododecane, CAS Registry Number 950-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-ethyl-5-methoxybicyclo[2.2.1]heptane, CAS registry number 122795-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, styrax absolute, CAS registry Number 8024-01-9, RIFM ID 6877.K2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α,α-dimethyl-p-ethylphenylpropanal, CAS Registry Number 67634-15-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α-hexylcinnamaldehyde, CAS Registry Number 101-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-octalactone, CAS Registry number 104-50-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methoxybenzoic acid, CAS Registry Number 100-09-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl acetate, CAS Registry Number 1191-16-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-hexalactone, CAS Registry Number 695-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, myristic acid, CAS Registry Number 544-63-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobutyric acid, CAS Registry Number 79-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-decalactone, CAS Registry Number 706-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-undecalactone, CAS Registry Number 104-67-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isovaleric acid, CAS Registry Number 503-74-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-nonalactone, CAS Registry Number 104-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

2nd update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-ol, CAS Registry Number 10339-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, linalool, CAS Registry number 78-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2H-indeno[4,5b] furan, decahydro-2,2,6,6,7,8,8-heptamethyl, CAS Registry Number 476332-65-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-dodecalactone, CAS Registry Number 2305-05-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, palmitic acid, CAS Registry number 57-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2,6,8-trimethylnonan-4-one, CAS Registry Number 123-18-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyric acid, CAS Registry number 116-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-4,9-decadienal, CAS Registry number 71077-31-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedrene, CAS Registry Number 11028-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 5-methyl-3-heptanone, CAS Registry Number 541-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, iris pallida oil, CAS registry number 8002-73-1, RIFM ID 265.A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 8H-indeno(4,5-B)furan,2,3,3a,4,5,5a,6,7,8a,9-decahydro-2,6,6,7,8,8-hexamethyl mixture of isomers, CAS Registry Number 338735-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-nonanone, CAS Registry Number 821-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-undecanone, CAS Registry Number 112-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-octanone, CAS registry number 106-68-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-heptanone, CAS Registry Number 110-43-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-heptalactone, CAS Registry Number CAS # 105-21-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-valerolactone, CAS Registry Number 108-29-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, lauric acid, CAS Registry Number 143-07-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-octanone, CAS Registry Number 111-13-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, benzoin infusion, Sumatra, CAS Registry Number 9000-05-9, RIFM ID 104-K2.31 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-heptanone, CAS Registry Number 123-19-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-heptanone, CAS Registry Number 106-35-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, myrtenol, CAS Registry Number 515-00-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylpropionic acid, CAS registry number 501-52-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexyl phenylacetate, CAS Registry Number 5421-17-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl cyclohexadiene (mixture of isomers), CAS Registry Number 30640-46-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanoic acid, CAS Registry Number 334-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 5-methyl-5-propyl-2-(1-methylbutyl)-1,3-dioxan, CAS Registry Number 80480-24-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanoic acid, CAS Registry Number 124-07-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-isopropylacetophenone, CAS Registry Number 645-13-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonanoic acid, CAS Registry Number 112-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4H-4a,9-methanoazuleno[5,6-d]-1,3-dioxole, octahydro-2,2,5,8,8,9a-hexamethyl-, (4aR,5R,7aS,9R)-, CAS Registry Number 211299-54-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, spiro[5.5]undec-8-en-1-one, 2,2,7,9-tetramethyl-, CAS Registry Number 502847-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-tolyl 3-methylcrotonate, CAS Registry Number 24700-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, CAS Registry Number 142-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-1,3-dioxolane, CAS Registry Number 33941-99-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-hydroxyacetophenone, CAS Registry Number CAS # 118-93-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-isopropyl-2-methoxy-1-methylbenzene, CAS Registry Number 6379-73-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1-ethynylcyclohexyl acetate, CAS Registry Number 5240-32-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,5,9b-tetrahydroindeno[1,2-d]-1,3-dioxine, CAS Registry Number 18096-62-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenyl-1-propanol, CAS Registry Number 122-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzaldehyde, CAS Registry Number 100-52-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzeneacetonitrile, a-butylidene-, (Z), CAS Registry Number 130786-09-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, geraniol, CAS registry number 106-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenoxyethanol, CAS Registry number 122-99-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl alcohol, CAS Registry Number 100-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-, methyl ester, CAS registry number 111753-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 4-carvomenthenol, CAS Registry Number 562-74-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-tert-butylcyclohexyl acetate, CAS registry number 88-41-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-tert-butylcyclohexyl acetate, CAS Registry Number 31846-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexyl acetate, CAS Registry Number 32210-23-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, phenyl salicylate, CAS Registry Number 118-55-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, fenchone, CAS Registry Number 1195-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, phenethyl acetate, CAS registry number 103-45-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal diethyl acetal, CAS Registry Number 7779-94-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amylcyclohexyl acetate (mixed isomers), CAS Registry Number 67874-72-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanal dimethyl acetal, CAS Registry Number 10022-28-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl hexanoate, CAS Registry Number 7779-23-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylundecanal dimethyl acetal, CAS Registry Number 68141-17-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry number 141-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-isobutylquinoline, CAS registry number 93-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-methyl quinoline, CAS registry number 91-63-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyisooctane, CAS Registry Number 69178-43-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonane, 1,1-diethoxy-, CAS Registry Number 54815-13-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1,1-diethoxy-3,5,5-trimethylhexane, CAS registry number 86198-35-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(methylpropyl)quinoline, CAS registry number 1333-58-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanal dimethyl acetal, CAS Registry Number 7779-41-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-isopropylphenol, CAS Registry Number 99-89-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-buten-2-one, 4-(2,2,3-trimethyl-6-methylenecyclohexyl)-, CAS registry number 79-68-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, heptanal dimethyl acetal, CAS registry number 10032-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyhexane, CAS registry number 3658-93-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-acetyl-5-methylfuran, CAS Registry Number 1193-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isophytol, CAS Registry Number 505-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-furyl methyl ketone, CAS Registry Number 1192-62-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, savory winter oil, CAS Registry Number 90106-57-3, RIFM ID 1181-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho wood oil, CAS Registry Number 8022-91-1, RIFM ID 217-D2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, dimethylcyclohex-3-ene-1-carbaldehyde (isomer unspecified), CAS Registry Number 27939-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-2-(4-methyl-3-cyclohexen-1-yl)-5-hepten-2-ol, CAS Registry Number 515-69-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, maltol, CAS registry number 118-71-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(5,5,6-trimethylbicyclo[2.2.1]hept-2-yl)cyclohexan-1-ol, CAS registry number 3407-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl valerate, CAS Registry Number 10361-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isocyclocitral, CAS Registry Number 1335-66-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, ho leaf oil, CAS Registry Number 8022-91-1, RIFM ID 217-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho bark oil, CAS registry number 8022-91-1, RIFM ID 217-C2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl formate, CAS Registry Number 104-57-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyheptane, CAS Registry Number 688-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-octanol, CAS registry number 111-87-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,6,7,8,8a-hexahydro-1,4-methanonaphthalen-5(1H)-one, CAS Registry Number 51519-65-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl hexanoate, CAS registry number 540-07-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecanal, CAS Registry Number 112-44-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, N-benzoylanthranilic acid, CAS Registry Number 579-93-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecyl alcohol, CAS Registry Number 112-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tridecanol, CAS Registry Number 112-70-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, lauryl alcohol, CAS Registry Number 112-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexyl alcohol, CAS Registry Number 111-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl maltol, CAS Registry Number 4940-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyrophenone, CAS Registry Number 495-40-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolyl phenylacetate, CAS Registry Number 101-94-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl decanoate, CAS Registry Number 110-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-decanol, CAS registry number 112-30-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, clove bud absolute, CAS Registry Number 8000-34-8, RIFM ID 583-F2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonyl alcohol, CAS Registry Number 143-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methoxy dicyclopentadiene carboxaldehyde, CAS Registry Number 86803-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octahydro-4,7-methano-1H-indenecarbaldehyde, CAS Registry Number 30772-79-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, acetophenone, CAS Registry number 98-86-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Sage oil, Spanish, CAS Registry Number 8022-56-8, RIFM ID 479-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

2nd Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4” [Food Chem. Toxicol. 197 Supplement 1 (2024) 115141 ISSN 0278–6915] - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptyl alcohol, CAS registry number 111-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-acetoxy-2,5-dimethyl-3(2H)furanone, CAS Registry Number 4166-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl propionate, CAS Registry Number 105-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl propionate, CAS Registry Number 540-42-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(p-methoxyphenyl)-2-butanone, CAS Registry Number 104-20-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-6-nonenal, CAS registry number 2277-19-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylbutanal, CAS registry number 16251-77-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cyclohexanepropanol, α-ethyl-2,2,6-trimethyl-, CAS Registry Number 60241-52-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 3,7-dimethyl-6-octenoate, CAS registry number 2270-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (1aα,4α,7aα)-1a,3,3,4,6,6-hexamethyl-1a,2,3,4,5,6,7,7a-octahydronapth[3,3-b]oxirene, CAS Registry Number 94400-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cyclododecyl formate, CAS Registry Number 59052-82-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (Z)-4-dodecenal, CAS registry number 21944-98-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenylpropionaldehyde, CAS registry number 93-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4,5-dihydro-3(2H)thiophenone, CAS Registry Number 1003-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 9-undecenal, CAS Registry Number 143-14-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-methyl-benzenepentanal, CAS registry number 55066-49-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonanal, CAS registry number 124-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-4-decen-1-al, CAS Registry Number 65405-70-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl formate, CAS Registry Number 110-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 8-undecenal, CAS registry number 58296-81-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isovalerate, CAS Registry Number 1118-27-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexanal, CAS Registry Number 66-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-7-nonen-2-ol, CAS Registry Number 40596-76-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-(methoxymethyl)phenol, CAS Registry Number 5595-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, β-caryophyllene alcohol, CAS registry number 472-97-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, acetylcarene, CAS Registry Number 3608-11-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-heptenal, CAS Registry Number 6728-31-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl alcohol, CAS Registry Number 123-51-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-phenoxyethyl isobutyrate, CAS registry number 103-60-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isobutyrate, CAS Registry Number 78-35-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tetradecanol, CAS Registry Number 112-72-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-hexenoic acid, CAS Registry Number 4219-24-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonynoate, CAS Registry Number 111-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-cyclohexenyl)butanol, CAS Registry Number 15760-18-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, dihydro-β-ionol, CAS Registry Number 3293-47-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolylacetaldehyde, CAS Registry Number 104-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-pinene, CAS Registry Number 127-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl crotonate, CAS Registry Number 56172-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4(2,2,3-trimethyl-3-cyclopentenyl)butanol, CAS Registry Number 72089-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl valerate, CAS Registry Number 2050-09-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octanal, CAS Registry Number 124-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tricyclo[3.3.1.1.(3.7)]decan-2-ol, 4-methyl-8-methylene-, CAS Registry Number 122760-84-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptanal, CAS registry number 111-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl butyrate, CAS Registry Number 51115-64-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl alcohol, CAS Registry Number 71-41-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, pentanoic acid, 2-methylbutyl ester, CAS Registry Number 55590-83-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,4-xylenol, CAS Registry Number 95-65-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl acetate, CAS Registry Number 624-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl butyrate, CAS Registry Number 539-90-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, decanal, CAS registry number 112-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedryl formate, CAS Registry Number 39900-38-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(4-methoxyphenyl)-3-methylbutan-2-one, CAS Registry Number 67828-19-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-(p-methoxyphenyl)-2-propanone, CAS Registry Number 122-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-2-hexenyl acetate, CAS Registry Number 2497-18-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, isolongifolene oxide, CAS Registry Number 26619-69-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-menth-8-en-2-one, CAS Registry Number 7764-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, l-menthyl (R,S)-3-hydroxybutyrate, CAS Registry Number 108766-16-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyl alcohol, CAS registry number 71-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tridecanal, CAS registry number 10486-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedr-8-ene epoxide, CAS Registry Number 13567-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl tiglate, CAS Registry Number 7785-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4′-tert-butyl-2′,6′-dimethylacetophenone, CAS Registry Number 2040-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl trans-2,cis-4-decadienoate, CAS registry number 3025-30-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl acetate, CAS Registry Number 123-92-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-hexadecanol, CAS Registry Number 36653-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl acetate, CAS Registry Number 110-19-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl salicylate, CAS Registry Number 65405-77-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-hepten-6-ol, CAS registry number 1569-60-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nopyl acetate, CAS registry number 128-51-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl butyrate, CAS Registry Number 106-27-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, piperonal, CAS Registry Number 120-57-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzothiazole, CAS Registry Number 95-16-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-cyclopropylmethyl-4-methoxybenzene, CAS registry number 16510-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2-methylenocta-6-enal, CAS registry number 22418-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(3-heptyl)-1,3-dioxolane, CAS Registry Number 4359-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methyl-3-pentenoate, CAS Registry Number 1617-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutanal diethyl acetal, CAS Registry Number 3842-03-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Improved nitrogen fertilizer management reduces nitrous oxide emissions in a northern Prairie cropland - D. Ferland; C. Wagner-Riddle; S.E. Brown; M. Bourgault; W. Helgason; R.E. Farrell; K.A. Congreves (Science of The Total Environment, 2024)

RIFM fragrance ingredient safety assessment, (4-methylphenoxy)acetaldehyde, CAS Registry Number 67845-46-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propyl alcohol, CAS Registry Number 71-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dibenzyl ether, CAS Registry number 103-50-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionyl acetate, CAS Registry Number 22030-19-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl cinnamate, CAS Registry Number 122-69-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-xylenol, CAS Registry Number 576-26-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl formate, CAS registry number 542-55-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-octynoate, CAS Registry Number 111-12-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanone 1,3-butylene glycol ketal, CAS Registry Number 6413-26-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, zingerone, CAS Registry Number 122-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-[(1-methylethoxy)methyl] phenol, CAS Registry number 96840-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, diethyl malonate, CAS registry number 105-53-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4,8-dimethylnona-3,7-dienyl)pyridine, CAS Registry Number 38462-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-propanediol, 2,2-dimethyl-, 1,3-diacetate, CAS registry number 13431-57-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(cis-3-hexenyloxy)propanenitrile, CAS Registry Number 142653-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl benzoate, CAS registry number 120-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4-methyl-3-penten-1-yl)-2(5H)-furanone, CAS Registry number 61315-75-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-butyl-4,4,6-trimethyl-1,3-dioxane, CAS registry number 54546-26-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-(2-tert-butyl cyclohexyloxy)-2-butanol, CAS Registry Number 139504-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methylbutyrate, CAS Registry Number 7452-79-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzyl salicylate, CAS registry number 118-58-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl benzoate, CAS registry number 6789-88-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isovalerate, CAS Registry Number 556-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cyclohexanecarboxylic acid, CAS Registry Number 98-89-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl isobutyrate, CAS registry number 97-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,8-dimethylnonan-2-ol, CAS registry number 70214-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl benzoate, CAS registry number 94-46-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isobutyrate, CAS registry number 547-63-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 10-undecenoic acid, heptyl ester, CAS registry number 68141-27-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methylcyclohex-3-enyl)-3-butenyl acetate, CAS registry number 6819-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-methyl-α-amyl cinnamic aldehyde, CAS Registry Number 84697-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl salicylate, CAS registry number 119-36-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-methylbutyrate, CAS Registry Number 868-57-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl salicylate, CAS Registry Number 2050-08-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-methyl-2-(1-methylpropyl)cyclohexyl acetate, CAS Registry number 72183-75-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl benzoate, CAS Registry Number 25152-85-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl salicylate, CAS Registry Number 87-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans-, CAS Registry Number 4625-90-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-2-pentanol, CAS registry number 108-11-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-dimethyl-4-heptanol, CAS registry number 108-82-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, heptyl acetate, CAS registry number 112-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-5-phenylpentanol, CAS Registry Number 25634-93-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl formate, CAS registry number 629-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl butyrate, CAS Registry Number 2639-63-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, furfural, CAS Registry Number 98-01-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl acetate, CAS Registry Number 112-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl formate, CAS registry number 112-32-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-ethyl-, trans-, CAS Registry Number 91069-40-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-mentha-1,8-dien-7-ol, CAS Registry Number 536-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-isopropyl-1,4-dimethylazulene, CAS registry number 489-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropyl-1-methylcyclohexene, CAS registry number 29350-67-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl α-ionone, CAS Registry Number 79-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, lauryl acetate, CAS Registry Number 112-66-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-methyl-, CAS Registry number 94201-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-5-phenylpentanol, CAS Registry Number 55066-48-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, nonyl acetate, CAS registry number 143-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl butyrate, CAS Registry Number 110-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(methylthio)hexyl acetate, CAS registry number 51755-85-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,2-dimethyl-3-phenylpropanol, CAS registry number 13351-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-(cis-3-hexenyl)dihydro-5-methyl-2(3H)furanone, CAS Registry Number 70851-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-phenyl anisole, CAS registry number 86-26-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl acetate, CAS registry number 105-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl linalool, CAS registry number 1113-21-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ionone (mixed isomers), CAS registry number 8013-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl salicylate, CAS Registry Number 118-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-phenyl-3-buten-2-ol, CAS registry number 17488-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl acetate, CAS registry number 108-21-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl propionate, CAS Registry Number 2445-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-butylcinnamaldehyde, CAS registry number 7492-44-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, decyl acetate, CAS Registry Number 112-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, musk ketone, CAS registry number 81-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, veratraldehyde, CAS Registry Number 120-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl butyrate, CAS Registry Number 638-11-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-hydroxybenzoic acid, CAS Registry Number 69-72-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylfurfural, CAS registry number 620-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl acetate, CAS registry number 142-92-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylpentanol, CAS registry number 92585-24-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylbutyraldehyde, CAS Registry Number 40654-82-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenal, CAS Registry Number 6789-80-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, pinus nigra oil, CAS Registry Number 8000-26-8, RIFM ID 1068-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl phenylacetate, CAS Registry Number 42288-75-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4,5,6,6-pentamethylheptan-2-ol, CAS registry number 87118-95-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-cyclohexadiene-1-carboxylic acid, 4,6,6-trimethyl-, ethyl ester, CAS Registry Number 100520-15-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(4H)-benzofuranone, 5,6-dihydro-3,6-dimethyl-, CAS Registry Number 80417-97-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, β-methylphenethyl alcohol, CAS Registry Number 1123-85-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N-ethyl-N-(3-methylphenyl)propionamide, CAS Registry Number 179911-08-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl cinnamate, CAS Registry number 1866-31-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-hexene, 1-[(2-methyl-2-propenyl)oxy]- (3Z)-, CAS Registry Number 292605-05-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, lavandin abrialis, CAS registry number 8022-15-9, RIFM ID 1048554 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, rotundone, CAS Registry Number 18374-76-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylheptenol, CAS Registry Number 1335-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,4-bis(ethoxymethyl)cyclohexane, CAS Registry Number 54889-63-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, bicyclo[2.2.1]heptan-2-ol, 1,3,3-trimethyl-, benzoate, CAS Registry Number 55066-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylbutyl hexanoate, CAS registry Number 2601-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, propanoic acid, 2-methyl-, cyclohexyl ester, CAS Registry Number 1129-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-yl acetate, CAS Registry Number 61931-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-heptanol, 3,6-dimethyl-, CAS registry number 1247790-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cyclohexanecarboxylate, CAS Registry Number 3289-28-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl butyrate, CAS Registry Number 78-36-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6-butyl-2,4-dimethyldihydropyrane, CAS Registry Number 24237-00-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-7-methoxyoctan-2-ol, CAS registry number 41890-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isopropyl-N,2,3-trimethylbutyramide, CAS registry number 51115-67-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, piperonyl acetate, CAS registry number 326-61-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-propylphenethyl alcohol, CAS registry number 705-73-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl heptanoate, CAS registry number 142-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-(4-methylphenoxy)ethanol, CAS Registry Number 15149-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nonanoyl 4-hydroxy-3-methoxybenzylamide, CAS Registry Number 2444-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl hexanoate, CAS Registry Number 123-68-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl alcohol, CAS Registry Number 60-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanol, a,ß-dimethyl-, CAS Registry Number 56836-93-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(2-oxopropyl)-2-pentylcyclopentanone, CAS Registry Number 40942-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1,3,3-trimethyl-2-norbornanyl acetate, CAS registry number 13851-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, tetrahydrogeranial, CAS Registry Number 5988-91-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isobornyl acetate, CAS Registry Number 125-12-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerolidyl acetate (isomer unspecified), CAS registry number 2306-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, oxacyclohexadecane-2,13-dione, CAS registry number 38223-29-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, (Z)-octadec-9-enol, CAS registry number 143-28-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl acetate, CAS registry number 115-95-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-naphthalenol, 1,2,3,4,4a,5,8,8a-octahydro-2,2,6,8-tetramethyl-, CAS Registry Number 103614-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl pivalate, CAS Registry Number 68039-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl isobutyrate, CAS Registry Number 67634-20-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, tricyclodecanyl acetate, CAS registry number 64001-15-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobornyl propionate, CAS Registry Number 2756-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl octanoate, CAS Registry Number 4230-97-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl formate, CAS registry number 115-99-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerol oxide, CAS Registry Number 1786-08-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-menthyl D-lactate, CAS registry number 59259-38-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl propionate, CAS registry number 144-39-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, trichloromethyl phenyl carbinyl acetate, CAS Registry number 90-17-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-hexen-1-ol, 5-methyl-2-(1-methylethenyl)-, CAS registry number 58461-27-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, dihydro-α-terpineol, CAS Registry Number 498-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-hexylcyclopentanone, CAS registry number 13074-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl isobutyrate, CAS registry number 10031-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, d,l-menthone 1,2-glycerol ketal, CAS Registry Number 63187-91-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-cyclohexyl-2-methyl-2-butanol, CAS registry number 83926-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4′-hydroxy-3′-methoxyacetophenone, CAS Registry Number 498-02-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2,2,4-trimethyl-4-phenyl-butane-nitrile, CAS Registry Number 75490-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, thymol, CAS Registry Number 89-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cinnamate, CAS Registry Number 103-36-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl benzoate, CAS Registry Number 5205-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylcyclooctyl carbonate, CAS Registry Number 61699-38-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-p-tolylethanol, CAS registry number 699-02-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,3,6-octatriene, CAS Registry Number 13877-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl isobutyrate, CAS Registry Number 59354-71-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl cinnamate, CAS Registry Number 3487-99-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butanol, CAS Registry Number 103-05-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanenitrile, 4-ethyl-α,α.-dimethyl-, CAS Registry Number 134123-93-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl 2,4-dihydroxy-m-toluate, CAS Registry Number 33662-58-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2H-1,5-benzodioxepin-3(4H)-one, 7-(1-methylethyl)-, CAS Registry Number 950919-28-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-ethylhexanoate, CAS Registry Number 2983-37-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl salicylate, CAS registry number 25485-88-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment,α-methylbenzyl alcohol, CAS registry number 98-85-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropylcyclohexanol, CAS Registry Number 4621-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde, diphenethyl acetal, CAS Registry Number 122-71-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl alcohol, CAS Registry Number 100-86-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl ethyl oxalate, CAS Registry Number 60788-25-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-tert-butylcyclohexyl carbonate, CAS Registry Number 67801-64-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2,3,6-trimethylcyclohexyl carbonate, CAS Registry Number 93981-50-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-octyl acetate, CAS registry number 4864-61-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, exo-2-[(1,7,7-trimethylbicyclo[2.2.1]hept-2-yl)oxy]ethanol, CAS Registry Number 7070-15-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-propanol, reaction products with boron trifluoride and 5-ethylidenebicyclo[2.2.1]hept-2-ene, CAS registry number 90530-04-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-propanol, 2-methyl-3-[(1,7,7-trimethylbicyclo-[2.2.1]hept-2-yl)oxy]-, CAS Registry Number 128119-70-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-nonanediol acetate (mixed esters), CAS Registry Number 1322-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,12-tridecadienenitrile, CAS Registry Number 134769-33-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, 4-methyl-, CAS registry number 1561-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-ethyloctanoic acid, CAS registry number 16493-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylhexanoic acid, CAS registry number 4536-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylheptanoic acid, CAS registry number 1188-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl 2-methylvalerate, CAS Registry Number 6297-41-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N,N-diethyloctamide, CAS registry number 996-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl salicylate, CAS Registry Number 87-22-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzonitrile, 3,4-dimethyl-, CAS Registry Number 22884-95-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-allyl-2-methoxyphenyl benzyl ether, CAS Registry Number 57371-42-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,6-nonadien-1-ol, CAS Registry Number 76649-25-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methylpentanoate, CAS Registry Number 39255-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl cinnamate, CAS registry number 78-37-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 3,5,5-trimethylhexanoate, CAS Registry Number 67707-75-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methyloctanoic acid, CAS Registry Number 54947-74-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl 10-undecenoate, CAS Registry Number 109-42-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylvaleric acid, CAS Registry Number 97-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-methylpentanoic acid, CAS registry number 105-43-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylnonanoic acid, CAS Registry Number 45019-28-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-ethylbutyric acid, CAS Registry Number 88-09-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis- and trans-p-1(7),8-menthadien-2-yl acetate, CAS registry number 71660-03-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, diethyldimethylcyclohex-2-en-1-one, CAS Registry Number 68845-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-phenyl-3-buten-1-yl acetate, CAS Registry Number 7306-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, spiro[1,3-dioxolane-2,8′(5′H)-[2H-2,4a]methanonaphthalene],hexahydro-1′,1′,5′,5′-tetramethyl-, [2′S-(2′α,4′aα,8′aα)]-, CAS Registry Number 154171-77-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-tolyl alcohol, CAS Registry Number 589-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylpentanoic acid, CAS Registry Number 646-07-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-2,3,4,5-tetramethylcyclohexen-1-one, CAS Registry Number 17369-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanol, 2-methoxy-4-propyl-, CAS Registry Number 23950-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 10-undecenoate, CAS Registry Number 692-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-tert-butyldihydrocinnamaldehyde, CAS Registry Number 18127-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl phenylacetate, CAS registry number 120-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(p-isopropylphenyl)propionaldehyde, CAS registry number 7775-00-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,3,5-trimethylcyclohexyl ethyl ether, CAS Registry Number 67583-77-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, triethyltrimethyl-2-cyclohexen-1-one, CAS Registry Number 68845-35-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, germacrene D, CAS Registry Number 23986-74-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-2-thiophenecarboxaldehyde, CAS registry number 13679-70-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl benzyl ether, CAS Registry Number 120-11-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl benzoate, CAS Registry Number 2049-96-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl vanillin isobutyrate, CAS Registry Number 188417-26-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-carvone, CAS Registry Number 6485-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl benzoate, CAS Registry Number 136-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-isopropyl phenylacetaldehyde, CAS Registry Number 4395-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl benzoate, CAS Registry Number 93-58-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-(1,1-dimethylpropyl)-4-ethoxy-, cis-, CAS Registry Number 181258-87-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-3-decen-5-ol, CAS Registry Number 81782-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoeugenol, CAS registry number 97-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 10-undecen-1-yl acetate, CAS Registry Number 112-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-pentenoic acid, CAS Registry Number 16957-70-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,10-dodecadienal, 3,7,11-trimethyl-, (3S,6E)-, CAS registry number 194934-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cuminyl nitrile, CAS registry number 13816-33-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (Z,Z)-1,1'-[ethylidenebis(oxy)]di(hex-3-ene), CAS Registry number 63449-64-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl benzoate, CAS Registry Number 93-89-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-5-phenyl-3-hexanone, CAS Registry Number 4927-36-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-1-(1-methoxypropoxy)hex-3-ene, CAS Registry Number 97358-54-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl undec-10-enoate, CAS registry number 111-81-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl cis-3-hexenyl acetal, CAS Registry Number 28069-74-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 9-decenyl acetate, CAS Registry Number 50816-18-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenol, 4-(3,6-dihydro-4-methyl-2H-pyran-2-yl)-2-methoxy-, CAS Registry Number 128489-02-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, eucalyptol, CAS Registry Number 470-82-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 5-hexyl-2-methyl-, CAS Registry Number 710-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dodecahydro-3,8,8,11a-tetramethyl-5H-3,5a-epoxynaphth[2,1-c]oxepin, CAS Registry Number 57345-19-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-3-buten-2-ol, CAS Registry Number 115-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-toluenethiol, CAS Registry Number 137-06-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-5-methyl-, methyl ester, CAS Registry Number 22717-57-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalool oxide, CAS Registry Number 1365-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Gill net catchability of walleye (Sander vitreus): Are provincial standards suitable for estimating adult density outside the region? - Adam G. Hansen; Michael W. Miller; Erik T. Cristan; Collin J. Farrell; Paul Winkle; Mandi M. Brandt; Kyle D. Battige; Jesse M. Lepak (Fisheries Research, 2023)

Stable carbon and nitrogen isotopes explain methylmercury concentrations in stream food webs of Lake George, New York (USA) - M. W. Swinton; P. K. Myer; M. F. Schaller; E. A. Pettitt; J. L. Farrell; S. A. Nierzwicki-Bauer (Ecotoxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Disturbance is complicated: Headward‐eroding saltmarsh creeks produce multiple responses and recovery trajectories - Fengrun Wu; Steven C. Pennings; Collin Ortals; Jennifer Ruiz; W. Reilly Farrell; Samuel M. McNichol; Christine Angelini; Amanda C. Spivak; Merryl Alber; Chunfu Tong (Limnology and Oceanography, 2022)
Disturbances are one of the most important processes affecting natural systems, but there is a gap between simple conceptual models of disturbance and complex empirical studies. We studied the perturbation caused by headward‐eroding creeks in southeastern USA salt marshes. We measured disturbance responses (magnitude and recovery trajectory) of 19 variables. Some variables (shoot density, root biomass, snail density, soil pH, soil strength, soil temperature, elevation) declined sharply, while other variables (crab burrow density, soil organic matter, soil redox) increased sharply, in response to the burrowed and grazed conditions at the creek head. These variables recovered over subsequent years or decades. Other variables (shoot height, aboveground biomass, rhizome biomass, light interception) declined sharply in the creek head, then overshot control values before recovering. Some variables (benthic algae, soil salinity) did not appear to be disturbed by the creek head. As hypothesized, plants recovered before soils and snails. Disturbance magnitude and time to recovery were often greater directly adjacent to the new creekbank than for the same variables in a parallel transect further away from the creekbank, and in some cases variables never converged with control values, indicating a persistent state change. Reducing the dimensionality of the data set into principal component axes obscured the diverse ways in which different aspects of the system responded to and recovered from the perturbation. Our study illustrates the challenges in moving from simple conceptual models of disturbance to empirical studies in which multiple variables are likely to be affected differently and follow different recovery trajectories.

Advanced materials and technologies for supercapacitors used in energy conversion and storage: a review - M. I. A. Abdel Maksoud; Ramy Amer Fahim; Ahmed Esmail Shalan; M. Abd Elkodous; S. O. Olojede; Ahmed I. Osman; Charlie Farrell; Ala’a H. Al-Muhtaseb; A. S. Awed; A. H. Ashour; David W. Rooney (Environmental Chemistry Letters, 2021)
Supercapacitors are increasingly used for energy conversion and storage systems in sustainable nanotechnologies. Graphite is a conventional electrode utilized in Li-ion-based batteries, yet its specific capacitance of 372 mA h g −1 is not adequate for supercapacitor applications. Interest in supercapacitors is due to their high-energy capacity, storage for a shorter period and longer lifetime. This review compares the following materials used to fabricate supercapacitors: spinel ferrites, e.g., MFe 2 O 4 , MMoO 4 and MCo 2 O 4 where M denotes a transition metal ion; perovskite oxides; transition metals sulfides; carbon materials; and conducting polymers. The application window of perovskite can be controlled by cations in sublattice sites. Cations increase the specific capacitance because cations possess large orbital valence electrons which grow the oxygen vacancies. Electrodes made of transition metal sulfides, e.g., ZnCo 2 S 4 , display a high specific capacitance of 1269 F g −1 , which is four times higher than those of transition metals oxides, e.g., Zn–Co ferrite, of 296 F g −1 . This is explained by the low charge-transfer resistance and the high ion diffusion rate of transition metals sulfides. Composites made of magnetic oxides or transition metal sulfides with conducting polymers or carbon materials have the highest capacitance activity and cyclic stability. This is attributed to oxygen and sulfur active sites which foster electrolyte penetration during cycling, and, in turn, create new active sites.

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

A rainbow trout Oncorhynchus mykiss strain with higher aerobic scope in normoxia also has superior tolerance of hypoxia - Y. Zhang; T. M. Healy; W. Vandersteen; P. M. Schulte; A. P. Farrell (Journal of Fish Biology, 2018)
This study compared parr from three strains of rainbow trout Oncorhynchus mykiss to examine intraspecific variation in metabolic traits, hypoxia tolerance and upper thermal tolerance in this species. At the strain level, variation in absolute aerobic scope (AAS), critical oxygen level (O 2crit ), incipient lethal oxygen saturation (ILOS) and critical thermal maximum (CT max ) generally exhibited consistent differences among the strains, suggesting the possibility of functional associations among these traits. This possibility was further supported at the individual level by a positive correlation between ILOS and O 2crit and a negative correlation between O 2crit and AAS. These results indicate that intraspecific differences in hypoxia tolerance among strains of O. mykiss may be primarily determined by differences in the ability to maintain oxygen uptake in hypoxia and that variation in aerobic scope in normoxia probably plays a role in determining the ability of these fish to sustain metabolism aerobically as water oxygen saturation is reduced.

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Aluminum toxicity risk reduction as a result of reduced acid deposition in Adirondack lakes and ponds - Toby M. Michelena; Jeremy L. Farrell; David A. Winkler; Christine A. Goodrich; Charles W. Boylen; James W. Sutherland; Sandra A. Nierzwicki-Bauer (Environmental Monitoring and Assessment, 2016)

Seasonal migration of the starry smooth‐hound shark Mustelus asterias as revealed from tag‐recapture data of an angler‐led tagging programme - N. W. P. Brevé; H. V. Winter; H. M. J. Van Overzee; E. D. Farrell; P. A. Walker (Journal of Fish Biology, 2016)
The primary aim of this long‐term angler‐led tagging programme was to gain information about seasonal changes in distribution of the starry smooth‐hound shark Mustelus asterias , along the Dutch coast for management and conservation purposes. Between 2011 and 2014, M. asterias comprised 92·6% ( n = 2418) of the total elasmobranch catch ( n = 2612) by the licenced group of taggers within the Dutch Delta of which 2244 M. asterias were fin‐tagged with plastic rototags. Sex and total length ( L T ) composition inside the eastern tidal basin (Oosterschelde) were significantly different, i.e. more females and larger individuals, than outside indicating a pupping ground, which was confirmed by the capture of 30 newborn pups (≤32 cm). The distribution pattern of reported recaptured M. asterias (return‐rate 3·6%, n = 80) showed a circannual migration between summering in the southern North Sea and wintering in the English Channel and the Bay of Biscay, and suggests that M. asterias is philopatric. The Dutch angling season for M. asterias runs from approximately mid‐May to mid‐October when the water temperature is above 13° C. Recaptures of eight mature females, but no males in the Bay of Biscay, indicate partial spatial segregation by sex, where mature females migrate over larger distances than immature females and males. These observations, with the absence of recaptures in other known summering areas ( i.e. the Irish Sea and Bristol Channel), suggest that the southern North Sea is used by a separate population. Implications for management and recommendations to improve and expand the study approach are discussed.

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Comparing community structure on shells of the abalone Haliotis midae and adjacent rock: implications for biodiversity - Zannè Zeeman; George M. Branch; Daniel Farrell; Gavin W. Maneveldt; Deborah Robertson-Andersson; Deena Pillay (Marine Biology, 2013)

Introduced and indigenous fungi of the Ross Island historic huts and pristine areas of Antarctica - R. L. Farrell; B. E. Arenz; S. M. Duncan; B. W. Held; J. A. Jurgens; R. A. Blanchette (Polar Biology, 2011)

Reproductive biology of the starry smooth‐hound shark Mustelus asterias : geographic variation and implications for sustainable exploitation - E. D. Farrell; S. Mariani; M. W. Clarke (Journal of Fish Biology, 2010)
Examination of the reproductive biology of Mustelus asterias in the north‐east Atlantic Ocean highlighted apparent geographical variation in maturity, fecundity and ovarian cycle between Atlantic and Mediterranean populations. The stretch total length ( L ST ) and age at 50% maturity for Atlantic males and females were estimated at 78 cm L ST and 4–5 years and 87 cm L ST and 6 years, respectively. Size at maturity of females was considerably smaller than in Mediterranean specimens (96 cm L ST ). Ovarian fecundity ranged from eight to 27 oocytes and uterine fecundity from six to 18 embryos. The gestation period was c. 12 months, followed by a resting period of c. 12 months, resulting in a biennial cycle. Females stored sperm in the oviducal gland and, unlike Mediterranean specimens, no uterine compartments were observed in Atlantic specimens. This study reveals the existence of strong, possibly adaptive, divergence in life‐history traits in an elasmobranch, whose northern populations may be more susceptible to overexploitation than previously believed.

Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.

Endoglucanase‐producing fungi isolated from Cape Evans historic expedition hut on Ross Island, Antarctica - Shona M. Duncan; Roberta L. Farrell; Joanne M. Thwaites; Benjamin W. Held; Brett E. Arenz; Joel A. Jurgens; Robert A. Blanchette (Environmental Microbiology, 2006)
Summary Early explorers of Antarctica’s Heroic Era erected wooden buildings and brought large quantities of supplies to survive in Antarctica. The introduction of wood and other organic materials provided nutrient sources for fungi that were indigenous to Antarctica or were brought in with the materials and adapted to the harsh conditions. Seventy‐two isolates of filamentous fungi were cultured on selective media from interior structural wood of the Cape Evans historic hut and 27 of these screened positive for the ability to degrade carboxymethyl cellulose (CMC). Four non‐CMC‐degrading isolates were added to a group of 14 CMC‐degrading isolates for further study, and endo‐1, 4‐β‐glucanase activity was demonstrated in the extracellular supernatant from all of these 18 isolates when grown at 4°C, and also when they were grown at 15°C. Isolates of Penicillium roquefortii and Cadophora malorum showed preference for growth at 15°C rather than 25°C or 4°C indicating psychrotrophic characteristics. These results demonstrate that cellulolytic filamentous fungi found in Antarctica are capable of growth at cold temperatures and possess the ability to produce extracellular endo‐1, 4‐β‐glucanase when cultured at cold and temperate temperatures.

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)